Development of the emulsion protein-fat system composition - Matveeva, Tatiana; Stankevych, Serhii; Kalyna, Viktoriia; Chaika, Tetiana; Dikhtyar, Aliona; Omelchenko, Svetlana; Kotliar, Oleh; Shubina, Lidiia; Novozhylova, Tetiana; Zolotukhina, Olena (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the study is the technological indicators of the emulsion protein-fat system developed on the basis of oilseeds and their processing products. The research problem is the need to stabilize the emulsion of the protein-fat system of plant origin. The solution to the problem of adjusting the technological indicators of emulsion protein-fat systems based on flax seeds and soybean meal is considered, in particular, the stability of the emulsion and resistance to oxidative damage. An emulsion protein-fat system with an increased content of ω-3 polyunsaturated fatty acids (ALA) based on a mixture of flax seeds and soybean meal is developed. The influence of the ratio of raw materials on the stability of the emulsion system is investigated. It was found that the rational ratio of flax seeds (40 %) and soybean meal (60 %) provides high resistance of the lipid component to oxidative damage, which is confirmed by the increase in the peroxide value by only 0.9 mmol ½O/kg after 30 days of storage. The effect of stabilizers – xanthan gum (0.5 %) and polyoxyethylene (20) sorbitan monolaurate (0.2 %) – on the stability of the emulsion protein-fat system during 30-day storage at a temperature of 4 °C was studied. The emulsion system of the developed composition is characterized by a lower protein content compared to the reference sample (by 8 %), however, this disadvantage is compensated by the balance of the fatty acid composition, a significantly higher content of ω-3 PUFA (9.8 % vs. 0 %) and lipids (17.7 % vs. 1.1 %). Such characteristics significantly increase its nutritional value. The developed protein-fat system has significant potential for implementation in the food industry, contributing to the creation of new products with a high ALA content and expanding the range of emulsion products that meet modern standards of healthy nutrition